DENTIFICATION AND TOXICITY TEST OF CITRONELLAL FROM CYMBOPOGON NARDUS LEAFS AS ANTIFEEDANT OF TOWARD THRIPS IN JATROPHA CURCAS - M, Iqbal Fikri (ALCHEMY, 2012)
The aim research is to identification citronellal compound from Cymbopogon nardus  leafs using gas chromaatograph – mass spectra (GC-MS) and showes variation consentration and time contack of citronellal compounds at toxicity test of thrips pest at Jatropha curcas using variation concentration. The result of fractioned destilation get 3 fractions; fraction I (2-110-C), fractions II (111-128 C) and fraction III (128-130o C) have same property with citronellal. Identification result of GC-MS showed that citronellal concentrated in fraction was 13 %. Toxicity testing given not significant different. At concentrate 40 mL/ L of citronellal in water destilat have contact poison because have kille thrips pest 85 % at 24 hours. But, at concentrate 5 ml/L, 10 ml/L, dan 20 ml/L air of citronellal in work as stomact poison, because just can kill less 50 % thrips pest at 24 hours after observed mortality value is 21,6 %, 8 % and 40 %.Key word: Identification, citronellal, cymbopogon, jatropha.